Fatty Acid Composition of Some Medicago L. (Fabaceae) Species From Turkey - Bakoglu, A.; Bagci, E.; Kocak, A.; Yuce, E. (Asian Journal of Chemistry, 2010)
The seed oils of five Medicago species (Medicago lupulina, Medicago sativa, M. minima var minima, M. rotata var. eliezeri, M. rigidula var. rigidula) (Fabaceae) were investigated for their fatty acid composition. The fatty acid composition of these five different species were determined by gas chromatography of the methyl esters of their fatty acids. The seed oils of Medicago species contained palmitic acid (10.79-19.18%), among the saturated acids with a small amount of stearic acid and arachidic acid. The major unsaturated fatty acids found in the seed oils were linolenic acid (43.69-25.51%) and linoleic acid (41.95-23.99%). Unsaturated fatty acid concentrations of Medicago species were found higher than the saturated fatty acid concentration. The results showed that Medicago patterns has linoleic-linolenic and oleic-palmitic type fatty acid. The result were discussed in means of renewable resources and chemotaxonomy.
Keywords: Medicago; Seed; Fatty Acid; Renewable resources; Chemotaxonomy